An unusual discursive relation: the influence of Cat Stevens’ Buddha and the Chocolate Box on Enrique Lafourcade’s Buddha y los chocolates envenenados - Fuentes Retamal, Pablo (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This article offers an interpretation of the novel Buddha y los chocolates envenenados (1997) by the Chilean writer Enrique Lafourcade, in relation with the music album Buddha and the Chocolate Box (1974) by the singer-songwriter Cat Stevens. The methodology, firstly, identifies the literary devices chosen by the storyteller to stablish discursive bonds with Stevens’s work, then, explains how these stylistic procedures take place in the plot. This plan of action lets prove how, and, to what extent, Steven’s production influenced the writer’s novel. The contribution of this case study aims to start a line of research which, until now, had not been explored by the literary critics. Finally, some projections are proposed whose execution will let determine the importance of Lafourcade’s musical imaginary in his own narrative work.